Transformasi Evaluasi Kinerja Pengelolaan Lingkungan Hidup di Indonesia: Dari Akuntabilitas Administratif Menuju Evaluasi Reflektif dan Berbasis Pembelajaran - Vandasari Vandasari (Pelantar Press, 2026)
This study examines the transformation of performance evaluation in environmental governance in Indonesia from an administrative accountability paradigm toward a reflective and learning-based approach. Using literature review, regulatory review, and conceptual synthesis, the study identifies a structural gap between the normative function of evaluation as a policy-learning instrument and its dominant use as a document-based accountability mechanism. The findings show that current evaluation practice is still driven by compliance, scoring, and reporting, creating a performance paradox in which improving indicators do not necessarily signal substantive environmental improvement. A phased reform is proposed through logic model integration, causal analysis, follow-up mechanisms, and evaluator capacity building. Transforming evaluation into a reflective instrument is essential to strengthen adaptive governance and improve sustainable environmental management